Identification of COVID 19 Risks of Micro, Small and Medium Scale Tourism Business Actors (MSMEs) in the Pangandaran Beach Area - Indah Rahmani, Natasha; Patabang, Melewanto; Untari, Rini (Journal of Indonesian Tourism and Development Studies, 2023)
The COVID-19 pandemic has impacted various sectors of the economy worldwide, including the tourism sector. The UNWTO (2020) reported that international tourist arrivals declined significantly by around 60-80% in 2020. As one of the regions in West Java Province that excels in the tourism sector, Pangandaran Regency was also affected. Based on the value of Gross Regional Domestic Product at Constant Prices in the accommodation and food and beverage supply sector, there is a decline of -2.32% in 2020 and a slight increase to 3.12% in 2021. However, it has not recovered as it did in 2019, when the rate was 9.28%. This study aims to investigate how MSMEs, specifically UMKM tourism business actors, in the Pangandaran Coastal Area have survived the COVID-19 pandemic outbreak. The method employed is deductive research, which involves collecting data by distributing questionnaires to 160 respondents from MSMEs in the tourism sector of the Pangandaran coastal area, using a purposive sampling technique, and applying risk management analysis. The results of this study show that most business actors closed temporarily due to the PPKM policy, while others adjusted their selling times, and some changed the type of business they offered. The most considerable and significant risk is the income component, which includes the number of visitors, the scarcity of funds, and the limited time available to sell. Meanwhile, the scarcity of capital goods, the number of workers, the health of sellers, and the health of human resources are relatively unaffected. The COVID-19 pandemic is the first pandemic to have occurred in this area in the last decade; there is no single research study on this topic prior to its emergence. The government and all the business actors are still figuring out the best way to keep their economy running.